PASAR TERPADU H. M. YUSI DI KANDANGAN - Nurmithasari, Nadya; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
M. Yusi Market is a regional market development plan from the government to improve the trade sector in the South Hulu Sungai regency. Kandangan Market as the main market has been unable to be developed to accommodate the large number of traders and the market location provided is not maximally utilized by traders because of the uncomfortable atmosphere because the application of market prototypes is not in accordance with local community buying and selling behavior. The architectural problem solving that is right for the Integrated Market H. M. Yusi in Kandangan is a comfortable market design and in accordance with the buying and selling behavior of market users in Kandangan. Behavioral Architecture method is an approach used to solve architectural problems in the integrated market of H. M. Yusi in Kandangan, namely by approaching the relationship of human behavior to the architectural environment as a consideration of the application of designs that will lead to improvements in the architectural environment. The study method includes the analysis of merchant behavior, buyer behavior and the relationship of behavior of traders and buyers to be able to adjust the needs and behavior of market users. Hygienic and cultural is a concept used to solve the problems of the application of integrated market area buildings that are comfortable and in accordance with market user behavior and Paiwakan Market concept is focus on wet market. The concept is applied to the design of circulation arrangement, achievement, building mass, material, facade ornaments and building utility systems.